PERAN KEGIATAN ROHANI KRISTEN DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMKN 2 SURAKARTA - Ayunda, Christydar Permata Bella; Juntak, Justin Niaga Siman (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
This study aims to explore the role of Christian religious activities in enhancing students’ learning motivation at SMK Negeri 2 Surakarta. The research employed a descriptive qualitative method using in-depth interviews, observations, and documentation as data collection techniques. The participants consisted of one Christian Religious Education (PAK) teacher as the spiritual mentor and fifteen Christian students from grades X and XI, including members of the Christian spiritual leadership team. The findings reveal that Christian spiritual activities including weekly worship services and character-building programs significantly influence students’ character formation and learning motivation. Christian values such as discipline, responsibility, honesty, perseverance, and spiritual awareness contribute to students’ diligence in learning and the development of positive study behaviors. Elements within worship, such as sermons, prayer, and praise, were found to provide inner peace, reduce stress, and generate intrinsic motivation for students to overcome academic challenges. Character-building activities also foster behavioral improvements, reflected in increased discipline, focus, and academic performance. This study concludes that Christian religious activities are not merely religious routines but serve as important instruments for developing students’ spirituality and moral character, which directly enhance their learning motivation. The findings highlight the need for schools and Christian Religious Education teachers to design more creative, relevant, and sustainable spiritual programs that support both academic growth and character development. ABSTRAK Penelitian ini bertujuan untuk memahami peran kegiatan rohani Kristen dalam meningkatkan motivasi belajar siswa di SMK Negeri 2 Surakarta. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara mendalam, observasi, dan dokumentasi. Informan penelitian terdiri dari 1 guru Pendidikan Agama Kristen (PAK) selaku pembina rohani serta 15 siswa Kristen dari kelas X dan XI, termasuk pengurus kegiatan rohani Kristen. Hasil penelitian menunjukkan bahwa kegiatan rohani Kristen, yang meliputi ibadah mingguan dan pembinaan karakter, memiliki pengaruh signifikan terhadap pembentukan karakter dan peningkatan motivasi belajar siswa. Nilai-nilai Kristiani seperti disiplin, tanggung jawab, kejujuran, ketekunan, serta kesadaran spiritual mendorong siswa untuk lebih tekun dalam belajar dan mengembangkan perilaku belajar positif. Unsur-unsur dalam ibadah seperti firman Tuhan, doa, dan pujian terbukti menumbuhkan ketenangan batin, mengurangi stres, serta menghadirkan dorongan intrinsik bagi siswa untuk mengatasi kesulitan akademik. Pembinaan karakter juga berkontribusi pada perubahan perilaku siswa, terlihat dari meningkatnya kedisiplinan, fokus belajar, serta peningkatan nilai akademik. Penelitian ini menegaskan bahwa kegiatan rohani Kristen bukan sekadar rutinitas religius, melainkan sarana pembentukan spiritualitas dan moral yang berdampak langsung pada kualitas motivasi belajar siswa. Temuan ini dapat menjadi dasar bagi sekolah dan guru PAK untuk mengembangkan program rohani yang lebih kreatif, relevan, dan berkelanjutan guna mendukung perkembangan akademik dan karakter siswa.